BN/ZIF-8 derived carbon hybrid materials for adsorptive desulfurization: Insights into adsorptive property and reaction kinetics. (15th March 2021) - Mu, Liping; Luo, Jing; Wang, Chao; Liu, Jixing; Zou, Yiru; Li, Xiaowei; Huang, Yan; Wu, Peiwen; Ji, Haiyan; Zhu, Wenshuai
Graphical abstract: Adsorptive desulfurization of DBT on BN/ZIF-8 derived carbon hybrid materials. Highlights: BN/ZIF-8 derived carbon hybrid materials were prepared by a facile pyrolysis method. High DBT adsorptive capacity (35.6 mg S g −1 ) was obtained. Synergistic effects of Lewis acid-base and π-π interactions for ADS performances. Abstract: Adsorption of stubborn sulfides from fuels is a feasible desulfurization strategy to obtain clean fuels, however, the exploration of efficient adsorbents to achieve this target remains a formidable challenge. Here, a hybrid nanocomposite comprising carbon-doped boron nitride (BN) and ZIF-8 derived carbon was constructed through a facile one-pot pyrolysis method. Thanks to the hierarchical porous structure and more exposed Lewis acid sites, the obtained adsorbent gave remarkable desulfurization performance for dibenzothiophene (DBT, 35.6 mg S/g), which was superior to that of the state-of-the-art carbon-doped BN reported under similar conditions so far. Moreover, the as-prepared absorbent exhibited impressive adsorptive capacity for 4-methyldibenzothiophene (4-MDBT) and 4, 6-dimethyldibenzothiophene (4, 6-DMDBT). Therefore, the BN-C hybrid materials presented here hold great promise for adsorptive desulfurization, as well as other related fields.